Better Early than Never – The Effects of Anticipated Gift Tax Changes on Business Transfers - Richard Winter; Jan Zental (CESifo GmbH, 2025)
Wealth transfer taxes can be important instruments to counter increasing wealth inequality. Yet, inter-generational business transfers, whose distribution is particularly concentrated at the top, are inherently difficult to tax. Many countries treat this asset class preferentially to avoid overburdening family firms, and sophisticated tax avoidance strategies by business owners exploit this preferential treatment to erode the tax base. We analyse how business transfers react to anticipated changes in such preferential tax treatment using administrative data at the individual-transfer level from the universe of German gift tax assessments. We find strong and rapid timing responses of business transfers to expected tax changes. We show that the response is stronger for higher-valued transfers and find heterogeneity in transfer characteristics consistent with a tax avoidance motive. We further estimate that the amount of foregone gift tax revenue due to timing responses is up to 2.8 times the size of actual annual inheritance and gift tax revenue.
Keywords: H00; H23; H25; H26; K34; D80; D81; 330; wealth transfer tax avoidance; business owners; tax uncertainty